The novel actin/focal adhesion-associated protein MISP is involved in mitotic spindle positioning in human cells - Maier, Bettina; Kirsch, Michael; Anderhub, Simon; Zentgraf, Hanswalter; Krämer, Alwin (Cell cycle, 2013)
Accurate mitotic spindle positioning is essential for the regulation of cell fate choices, cell size and cell position within tissues. The most prominent model of spindle positioning involves a cortical pulling mechanism, where the minus end-directed microtubule motor protein dynein is attached to the cell cortex and exerts pulling forces on the plus ends of astral microtubules that reach the cortex. In nonpolarized cultured cells integrin-dependent, retraction fiber-mediated cell adhesion is involved in spindle orientation. Proteins serving as intermediaries between cortical actin or retraction fibers and astral microtubules remain largely unknown. In a recent genome-wide RNAi screen we identified a previously uncharacterized protein, MISP (C19ORF21) as being involved in centrosome clustering, a process leading to the clustering of supernumerary centrosomes in cancer cells into a bipolar mitotic spindle array by microtubule tension. Here, we show that MISP is associated with the actin cytoskeleton and focal adhesions and is expressed only in adherent cell types. During mitosis MISP is phosphorylated by Cdk1 and localizes to retraction fibers. MISP interacts with the +TIP EB1 and p150glued, a subunit of the dynein/dynactin complex. Depletion of MISP causes mitotic arrest with reduced tension across sister kinetochores, chromosome misalignment and spindle multipolarity in cancer cells with supernumerary centrosomes. Analysis of spindle orientation revealed that MISP depletion causes randomization of mitotic spindle positioning relative to cell axes and cell center. Together, we propose that MISP links microtubules to the actin cytoskeleton and focal adhesions in order to properly position the mitotic spindle.
Gesehen am 15.06.2021